Rice Soil Fertility Classification in the Mekong Delta, Vietnam - Vo Quang Minh; Le Quang Tri; Le Van Khoa; Thai Thanh Du; Pham Thanh Vu; Tran Van Dung; Nguyen Minh Dong (AGRIVITA, Journal of Agricultural Science, 2023)
The rice crop intensification led to soil degradation and yield decline in the Mekong Delta, Vietnam. Therefore, it is necessary to classify soil fertility and identify the constraints for proper soil use. The soil legend classified by World Reference Based was converted to the Fertility Capability Classification system. The soil constraints and recommendations for appropriate services are suggested. The findings indicate seven primary soil categories, ten diagnostic layers, three diagnostic features, and three diagnostic materials in the rice soils of the Mekong Delta. Eleven soil constraints were found, most of which were associated with acid sulfate and saline soils. These constraints included low acidity, strong acidity, low available P, high P fixation, high potential Fe toxicity, slightly actual acid sulfate and shallow potential acid sulfate, deep potential acid sulfate, slight salinity, and strong salinity, low mineral supply capacity, limited organic carbon content, and low nutrient retention capacity. Reclamation of acid sulfate and saline soils by leaching soil toxicity and boosting soil nutritional status with organic matter and P, K treatment were recommended for degraded, acid sulfate, and saline soils.